The Construction of a Risk Prediction Model Based on Neural Network for Pre-operative Acute Ischemic Stroke in Acute Type A Aortic Dissection Patients - Zhao, Hongliang; Xu, Ziliang; Zhu, Yuanqiang; Xue, Ruijia; Wang, Jing; Ren, Jialiang; Wang, Wenjia; Duan, Weixun; Zheng, Minwen (Frontiers in Neurology, 2021)
OBJECTIVE To establish a pre-operative acute ischemic stroke risk (AIS) prediction model using the deep neural network in patients with acute type A aortic dissection (ATAAD) METHODS Between January 2015 and February 2019, 300 ATAAD patients diagnosed by aorta CTA were analyzed retrospectively. Patients were divided into two groups according to the presence or absence of pre-operative AIS. Pre-operative AIS risk prediction models based on different machine learning algorithm was established with clinical, transthoracic echocardiography (TTE) and CTA imaging characteristics as input. The performance of the difference models was evaluated using the receiver operating characteristic (ROC), precision-recall curve (PRC) and decision curve analysis (DCA). RESULTS Pre-operative AIS was detected in 86 of 300 patients with ATAAD (28.7%). The cohort was split into a training (211, 70% patients) and validation cohort (89, 30% patients) according to stratified sampling strategy. The constructed deep neural network model had the best performance on the discrimination of AIS group compare with other machine learning model, with an accuracy of 0.934 (95%CI: 0.891-0.963), 0.921 (95%CI: 0.845-0.968), sensitivity of 0.934, 0.960, specificity of 0.933, 0.906 and AUC of 0.982 (95%CI: 0.967-0.997), 0.964 (95%CI: 0.932-0.997) in the training and validation cohort respectively. CONCLUSION The established risk prediction model based on the deep neural network method may have the big potential to evaluate the risk of pre-operative AIS in patients with ATAAD.